2021
DOI: 10.1136/oemed-2021-107487
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of the SARS-CoV-2 antibody in healthcare workers: a multicentre cross-sectional study in 10 Colombian cities

Abstract: BackgroundHealthcare workers are at increased risk of infection due to occupational exposure to SARS-CoV-2-infected patients. The objective of this study was to determine the seroprevalence of SARS-CoV-2 in healthcare workers in Colombia.MethodsThis study is a cross-sectional study focused on estimating the seroprevalence of SARS-CoV-2 antibodies in healthcare workers from 65 hospitals in 10 cities in Colombia during the second semester of 2020. The seroprevalence was determined using an automated immunoassay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
2
6
2
Order By: Relevance
“…The seroprevalence reported globally range between 3% and 51%, increasing with the progression of the pandemic [ 1 , 5 7 ]. In our study, the seroprevalence was lower than that reported for Bogotá’s population (29.9%) [ 20 ] and that previously reported for HCWs in Bogotá (34%) [ 14 ] in studies with similar time frames as our study. This may indicate that in healthcare institutions with proper availability of PPE and adherence to its use, as in ours (97.4%), HCWs may have an infection risk similar to or lower than that in the community.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The seroprevalence reported globally range between 3% and 51%, increasing with the progression of the pandemic [ 1 , 5 7 ]. In our study, the seroprevalence was lower than that reported for Bogotá’s population (29.9%) [ 20 ] and that previously reported for HCWs in Bogotá (34%) [ 14 ] in studies with similar time frames as our study. This may indicate that in healthcare institutions with proper availability of PPE and adherence to its use, as in ours (97.4%), HCWs may have an infection risk similar to or lower than that in the community.…”
Section: Discussioncontrasting
confidence: 71%
“…Even though several studies have assessed the burden of SARS-CoV-2 infection in HCWs, data from low- and middle-income countries such as Colombia are scarce, especially concerning the incidence of SARS-CoV-2 and associated factors. In a previous study conducted in 10 major cities in Colombia, the seroprevalence of SARS-CoV-2 in the HCWs was 35% from September to November 2020 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The seroprevalence in the general population estimated in the SAPRIS study 12 in the same geographical area (Greater Paris) in May 2020, corresponding to M1 in the SEROCOV study, was significantly lower than in the SEROCOV first-line HCWs: 6.4% in the 20- to 59-year-old population of the SAPRIS study (using a similar anti-nucleoprotein assay and considering weak positive as positive as in SEROCOV) versus 13.3% in SEROCOV ( p < 0.0001). Previous published HCW surveys reported seroprevalence ranging from 3.4 to 38% 13 , 14 . However, the heterogeneity in type of HCW tested, type of assay used, period of testing and countries with incomparable SARS-CoV-2 epidemic burden precludes a face-to-face comparison.…”
Section: Discussionmentioning
confidence: 97%
“…The crude proportion shows the proportion of the participants who were reactive. To determine the real proportion of seroreactivity, an adjustment was performed based on the sensitivity and specificity of the ADVIA Centaur COV2, as previously reported [ 23 ]. The figure also presents the prevalence of total antibodies against COVID-19 during the study (days 0, 30, 60, 90, and 210).…”
Section: Resultsmentioning
confidence: 99%
“…The overall crude frequencies of seropositivity tests were estimated. Then crude seroprevalence was adjusted by using the Bayesian method in R V.2.21.2 (package RStan), using the sensitivity and specificity data reported in previous studies carried out by using a chemiluminescence immunoassay (CLIA) in Colombian populations [ 23 ]. The 95% Bayesian confidence intervals were obtained.…”
Section: Methodsmentioning
confidence: 99%